Effectiveness of nirsevimab immunization against RSV infection in preterm infants: a systematic review and meta-analysis - Xiaopeng Wang; Xiaopeng Wang; Xiaopeng Wang; Li Kong; Li Kong; Li Kong; Xueou Liu; Panpan Wu; Panpan Wu; Panpan Wu; Lulu Zhang; Lulu Zhang; et al. (Frontiers in Immunology)
BackgroundRespiratory Syncytial Virus (RSV) is one of the primary pathogen responsible for severe lower respiratory tract infections in preterm infants, placing a significant burden on patients, their families, and society. Nirsevimab, a recently developed RSV monoclonal antibody, has demonstrated promising efficacy in this population according to preliminary studies. However, there remains a need for comprehensive systematic reviews and meta-analyses to evaluate the effectiveness of nirsevimab in preventing RSV-related lower respiratory tract infections in preterm infants.MethodsA search of the PubMed and EMBASE databases was conducted to identify randomized controlled trials (RCTs) and observational studies assessing the prevention of RSV infection in preterm infants using nirsevimab. Relevant data were extracted and subjected to meta-analysis.ResultsFive studies involving a total of 7,347 preterm infants (3,987 in the nirsevimab group and 3,360 in the control group) were included. The meta-analysis revealed that nirsevimab significantly reduced the incidence of medically attended RSV-associated lower respiratory tract infections (OR = 0.25; 95% CI: 0.15, 0.40; P < 0.0001) and hospitalizations due to RSV-associated lower respiratory tract infections (OR = 0.27; 95% CI: 0.19, 0.38; P < 0.0001).ConclusionNirsevimab significantly decreases the risk of RSV-related infection in preterm infants and represents a valuable intervention for RSV prevention in this vulnerable population.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025629937.